Death of a stranger - Perry, Anne. (New York : Ballantine Books, 2002)
When a railway magnate is murdered in a London brothel and three battered prostitutes seek medical attention at his wife's clinic, Private Investigator William Monk is drawn into a puzzle that may have something to do with his former life.
Keywords: Monk, William (Fictitious character) -- Fiction; Private investigators -- England -- London -- Fiction; London (England) -- Fiction; Historical fiction; Mystery fiction